Investigations into β2-adrenoceptor pharmacology: kinetic analysis, mechanotransduction and allosteric modulation - Cullum, Sean A. (2024)
The β2-adrenoceptor (β2AR) is a prototypical class A member of the G protein-coupled receptor (GPCR) superfamily of membrane-bound receptors. Activation of the β2AR is associated primarily with the relaxation of airway and vascular smooth muscle and has been targeted extensively by β-agonists to treat pulmonary diseases. This thesis has investigated several underexplored aspects of β2AR pharmacology to improve our understanding of the mechanisms underpinning GPCR action. Quantifying endogenous β2AR-mediated cAMP signalling kinetics in HEK293 cells revealed that partial (but not full) agonists exhibited reduced maximal initial rates of signal generation (IRmax) compared with their maximal responses (Emax), likely reflecting slower rates of receptor desensitisation. Moreover, preincubation of slowly dissociating antagonists greatly reduced agonist Emax and IRmax values due to hemi-equilibrium conditions. These findings were not observed upon β2AR overexpression because of increased receptor reserve. Kinetic analysis of β2AR responses has provided valuable new insights into ligand-receptor interactions. Receptor overexpression also exposed a mechanosensory function of the β2AR whereby a transient cAMP signal was measured after application of a sustained linear motion to cells, which may be physiologically relevant in the vascular system. This response was potentiated or inhibited by agonists and inverse agonists, respectively. Mutagenic removal of three N-glycosylation sites (Asn6, Asn15 and Asn187) resulted in a substantial reduction of the mechanical response, suggesting receptor extracellular N-glycan chains are responsible for conferring β2AR mechanosensitivity. Finally, functional characterisation of five β2AR-derived pepducins (ICL3-2, ICL3-7, ICL3-8, ICL3-9 and ICL1-15) uncovered possible allosteric agonist activity, although this was inconclusive due to the variability and small magnitude of responses. No evidence was found of pepducin binding to detergent-solubilised β2AR, however several pepducins modestly increased receptor dissociation rates of either F-propranolol (ICL3-7) or formoterol (ICL3-9, ICL1-15) in native membranes, indicative of allosteric modulation. This thesis contributes to a greater understanding of the kinetics of β2AR signalling, receptor mechanotransduction and allosteric modulation by pepducins.